PENGARUH MOTIVASI KERJA DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMAN 6 PENAJAM PASER UTARA-KALIMANTAN TIMUR - Waumi Waumi; Indra Prasetyo; Chamariyah Chamariyah (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to determine the description of work motivation, principal leadership style and performance of SMAN 6 Penajam Paser Utara teachers and to know the influence of work motivation and principal leadership style simultaneously and partially to the performance of teachers SMAN 6 Penajam Paser Utara. This research uses quantitative approach and explanatory research type. The population in this study is all teachers in SMAN 6 Penajam Paser Utara. The sample of this study amounted to 32 teachers. The sampling technique uses saturated samples and data collection methods using questionnaires. Methods of data analysis used descriptive analysis and multiple regression analysis. The results of this study indicate that there is simultaneous influence between work motivation and principal leadership style on teacher performance of SMAN 6 Penajam Paser Utara. There is also a partial influence between work motivation and principal leadership style on teacher performance of SMAN 6 Penajam Paser Utara. Keywords: work motivation, principal leadership style and teacher performance